2022
DOI: 10.1186/s12877-022-03644-w
|View full text |Cite
|
Sign up to set email alerts
|

Calf circumference predicts frailty in older adults: the Chinese longitudinal healthy longevity survey

Abstract: Background Although frailty is a common geriatric syndrome in old adults, a simple method to assess the degree of frailty in a person has not yet been established. In this study we have tried to establish the association between calf circumference (CC) and frailty among older Chinese people. Methods We used the data obtained from the 2014 edition of the Chinese Longitudinal Healthy Longevity Survey; 1216 participants aged ≥60 years were included fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Although the radiological modalities for assessing muscle mass are convincing in terms of accuracy compared with CC determination, CC measurement in the elderly additionally impresses with its valuable predictability of fall events, frailty, malnutrition, morbidity and mortality [ 16 , 21 25 ] . The anthropometric method for recording CC provides a viable and cost-effective option for diagnosing “confirmed sarcopenia” in the elderly according to the diagnostic algorithm of the EWGSOP-2 guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Although the radiological modalities for assessing muscle mass are convincing in terms of accuracy compared with CC determination, CC measurement in the elderly additionally impresses with its valuable predictability of fall events, frailty, malnutrition, morbidity and mortality [ 16 , 21 25 ] . The anthropometric method for recording CC provides a viable and cost-effective option for diagnosing “confirmed sarcopenia” in the elderly according to the diagnostic algorithm of the EWGSOP-2 guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the evidence has shown the importance of evaluating the circumferences of the upper and lower limbs, since they are an indicator of the progressive loss of muscle mass associated with aging (sarcopenia) (Cruz-Jentoft et al, 2019). In this sense, calf circumference is a reliable indicator of leg muscle mass, since a decrease in the circumference of this segment is associated with a greater risk of frailty and loss of FA, which could potentially contribute to the appearance of a physical disability (Xu et al, 2022). The findings of our study have shown that G1 presented a greater calf circumference than G2 (p < 0.05).…”
Section: Anthropometric Parametersmentioning
confidence: 99%
“…CFS demonstrates silhouette of patients representing particular functional status which physicians are able to evaluate frailty at a glance [ 18 ]. Calf circumference was a predictable marker of frailty [ 19 ]. Dementia Assessment Sheet for Community-based Integrated Care System 21-items (DASC-21) and 8-itmes (DASC-8) are simple questionnaire containing 21 or 8 questions evaluating cognition, ADL and instrumental ADL (IADL) associated with frailty and several CGA components [ 20 , 21 ].…”
Section: Frailty and Blood Pressure Targetsmentioning
confidence: 99%